Economic Theories and Models: a Contribution in Understanding Their Foundations - Emmanuel, NDINGA GO’O (International Journal of Scientific Research and Management (IJSRM), 2022)
The interest of discovering and unveiling the thoughts of great scholars, condensed in theories comes at the right time in order to understand the knowledge revealed during studies of social sciences, in particular economics. The main intention of this article is to make understand the ideas that led these authors to state them, taking into account the temporal spatial conditions of the corresponding eras. This led to the emergence of these ideologies. Which over time have been considered as framework laws of a constitution, or even more gospel words to follow and not to break. The answer to the question posed in the background, namely can we easily affirm that the theories and models designed by these authors are founded on the basis of facts and phenomena observed in their time? In other words: do these theories have a link with their times? Bring us to adopt a comparative analysis which allowed us to note that most of the results or constructions of models married the living ideology at that time. That the classics, for example, could only build models with reference to the functioning of their time, or that the Keynesians could only develop theories that matched the image of the facts observed at that time. Understanding this constructive process of theories and economic models will allow us, my liver, at the end of this look, to understand the reasons which animated the founders of these theories to state them. Better still, we will be able to envisage future visions and ideological thoughts of future generations, in view of the evolution of human behavior observed today.